Cloning and sequence analysis of a cDNA encoding rat preprocholecystokinin. - Deschenes, R J (1984)
Poly(A) RNA was isolated from a rat medullary thyroid carcinoma that exhibited high levels of immunoreactive cholecystokinin (CCK). Double-stranded cDNA was synthesized from the poly(A) RNA and inserted into the Pst I site of pBR322. Bacterial colonies containing CCK cDNA were identified using the hybridization probe d(T-C-C-A-T-C-C-A-N-C-C-C-A-T-G-T-A-G-T-C). The sequence of the probe was deduced from the known amino acid sequence of porcine CCK-8, Asp-Tyr-Met-Gly-Trp-Met-Asp-Phe-NH2. The nucleotide sequence of the cDNA complementary to the mRNA of rat preprocholecystokinin was determined. The cDNA contains 33 nucleotides in the 5'-noncoding region, 199 nucleotides in the 3'-noncoding region, and 345 nucleotides coding for a precursor to CCK, which is 115 amino acids (Mr, 12,826). Examination of the rat CCK gene revealed a suggested transcriptional control sequence analogous to the "TATA" sequence located 33 nucleotides upstream from a proposed transcriptional start site. The amino acid sequence of CCK-39 is flanked by both amino-terminal and carboxyl-terminal extensions. Analysis of CCK mRNA showed that it is approximately equal to 750 nucleotides long. CCK mRNA of the rat brain and intestine appeared to be identical in size to the CCK mRNA of the carcinoma.